Antibiotics in foods: Determination and quantification by HPLC with fluorescence detection - PENA, A. L.; SILVEIRA, M. L.; CASTILLO, B. (Ars Pharmaceutica (Internet), 1997)
The monitoring of food material s for antibiotic residues is an area of increasing concern and importance due to the potential impact on human health. Antibiotics are used in food-producing animals not only for treatment of disease, but also subtherapeutically to mantain health and promove growth. The use of unauthorized antibiotics or the failure to follow label directions for approved antibiotics, could result in unsafe antibiotic residues in food products. Therefore, monitoring antibiotic residues in food forms part of a general policy to prevent unnapproved uses of antibiotics. Liquid chromatography has become the analytical method of choice for the identification and quantification of antibiotic residues in food. Fluorescence detection has been proved to be a valuable tool for antibiotic residue analysis, where interferences from food. components must be reduced or eliminated, due of the higher specifity and sensitivity.